The Relationship of Knowledge and Family Planning Unmet Need Incidence in Couple of Reproductive Age - KD, Widiantar; NW, Ari Adiputri (Jurnal Kebidanan, 2023)
The Family Planning Program has a very strategic, comprehensive, and fundamental meaning in realizing healthy and prosperous Indonesian people and can significantly reduce fertility rates, although the Fertility Rate (TFR) is still increasing. This is due to the high unmet need for family planning (BKKBN, 2015). Unmet Need is a Fertile Age Couple who wants to delay having children for two years or more and does not want to have more children but is not an active family planning participant (BKKBN, 2016). This study aims to determine the relationship between knowledge and the incidence of family planning (KB) Unmet need in fertile-age couples (PUS) in Denpasar. The research design used was analytic observational with a cross-sectional approach. The research subjects used 96 fertile age couples in Denpasar City. The sampling technique used the proportional stratified random sampling method to determine the number of samples in each district. The analysis used was the Chi-Square test with 95% Confidence Interval (CI). The results showed that the value of p = 0.000 ≤ 0.05, so it can be concluded that knowledge has a significant relationship with the incidence of unmet need family planning in fertile age couples.Program Keluarga Berencana merupakan memiliki makna yang sangat strategis, komprehensif dan fundamental dalam mewujudkan manusia Indonesia yang sehat dan sejahtera serta secara nyata dapat menurunkan angka  fertilitas, walaupaun Tingkat Fertility Rate (TFR) masih mengalami peningkatan. Hal ini disebakan oleh karena tinginya kebutuhan ber KB yang tidak terpenuhi (BKKBN, 2015). Unmet Need adalah Pasangan Usia Subur (PUS) yang ingin menunda untuk memiliki anak selama dua tahun atau lebih dan tidak ingin memiliki anak lagi, namun tidak menjadi peserta KB aktif  (BKKBN, 2016). Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dengan kejadian Unmet need Keluarga Berencana (KB) pada Pasangan Usia Subur (PUS)  di Kota Denpasar. Rancangan  penelitian yang digunakan yaitu observasional analitik dengan pendekatan cross sectional. Subjek penelitian menggunakan 96 wanita Pasangan Usia Subur di Kota Denpasar. Teknik pengambilan sampel menggunakan metode proportional stratified random sampling untuk menentukan jumlah sampel di masing-masing kecamatan. Analisis yang digunakan adalah uji Chi- Square dengan Confidence Interval (CI) 95%. Hasil penelitian menunjukkan bahwa nilai p=0,000  ≤ 0,05, sehingga dapat disimpulkan bahwa pengetahuan memiliki hubungan yang  signifikan  dengan  kejadian unmet need KB pada PUS.